(untitled) (Journal of Accessibility and Design for All, 2020)
Individuals using ambulation or wheeled assistive technologies encounter obstacles when accessing built environments. Although there are many environmental evaluations allowing the identification of these obstacles, very few take into consideration both outdoor and indoor environments. Since we know little about the environments of individuals with mobility impairments regarding their mobility assistive technologies (MAT) and mobility in general, the aim of the project was to objectively describe environmental obstacles encountered by mobility device users in two Canadian urban settings. Locations to be evaluated were nominated by community dwelling MAT users during focus groups in Quebec City (n=25 participants) and community forums in the Vancouver region (n=30-45). The measure of environmental accessibility (MEA) was used to evaluate the outdoor and indoor identified barriers. Relevant MEA sections were completed based on problems that were noted by MAT users, and non-compliant items were recorded. Nineteen locations (buildings and exterior spaces) in Quebec City and 20 in the Vancouver region were evaluated. Fifteen MEA sections were used in Quebec City and 12 in the Vancouver region (out of 29): curb ramps; sidewalk; parking; outdoor signage; doors; accessible routes; walls; obstacles; access ramps; handrails and guardrails; elevators; equipment (automatic teller machine); locker rooms; toilet, changing and shower stalls; and washrooms. Non-compliant items were similar in Quebec City and the Vancouver region. The most frequently encountered ones were similar in both locations. The most problematic MEA sections (with more non-compliant items) were access ramps and washrooms. This study provides a better understanding of the objective characteristics of outdoor and indoor environments impeding access among mobility device users, and consequently, the elements which should be considered for improvement.